2017
DOI: 10.26417/ejes.v8i1.p8-15
|View full text |Cite
|
Sign up to set email alerts
|

A Fresh Apple or a New Barrel: Business Ethics from an Individual to Corporate Level

Abstract: The moral nature of corporations has been discussed for a long time. But, since 2001, with enormous economic effects of the misconduct of some corporations this discussion gained another dimension, it moved into the public sphere, the subject became more sensitive. The anger and mistrust of the public toward business triggered legislators and corporations to take urgent action. For example, just after the collapse of Enron (2001) the American Congress passed the Sarbanes-Oxley Act (2002) that covers the respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Payne et al (2019) argues that the implementation of a code of ethics without its written commitment to it is ineffective. Thomas (2017) conducted research on the impact of codes of ethics on ethical behavior and confirmed theories regarding the existence of codes of ethics. Research has confirmed that it is not enough for codes of ethics to be developed, but that proper implementation is also needed.…”
Section: Theoretical Backgroundmentioning
confidence: 89%
“…Payne et al (2019) argues that the implementation of a code of ethics without its written commitment to it is ineffective. Thomas (2017) conducted research on the impact of codes of ethics on ethical behavior and confirmed theories regarding the existence of codes of ethics. Research has confirmed that it is not enough for codes of ethics to be developed, but that proper implementation is also needed.…”
Section: Theoretical Backgroundmentioning
confidence: 89%